2020
DOI: 10.21009/biosferjpb.v13n2.216-229
|View full text |Cite
|
Sign up to set email alerts
|

Edmodo as a solution to enhance student learning interest in high school biodiversity during the COVID-19 pandemic

Abstract: This study aims to improve the quality of learning by applying Edmodo's application at biodiversity class material of class 10 students in increasing student learning interest during Covid-19 period. Based on observations at SHS 3 Kerinci regency in Jambi province, Indonesia it was known that students' interest in learning biology was still low. This was due to the lack of availability of existing facilities and the learning process that is still through lectures and questions and answers. Students were less i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Supported by the research of Sulisworo & Agustin (2017), Ibrahim & Suardiman. (2014), Iwantara et al (2014), Aurora (2019), Wicaksana et al (2020), andSyarif (2012) said that online learning could increase student learning motivation and will increase understanding learners.…”
Section: Resultsmentioning
confidence: 99%
“…Supported by the research of Sulisworo & Agustin (2017), Ibrahim & Suardiman. (2014), Iwantara et al (2014), Aurora (2019), Wicaksana et al (2020), andSyarif (2012) said that online learning could increase student learning motivation and will increase understanding learners.…”
Section: Resultsmentioning
confidence: 99%
“…This low interest in learning during the pandemic was in line with the previous researches of Sulistiawati (2020) which concluded that students' interest in learning has decreased during the pandemic. Wicaksana, et al (2020) also concluded that students' interest in learning biology during the pandemic was low.…”
Section: Interest In Studying Biology Of Students During the Covid-19 Pandemicmentioning
confidence: 99%
“…For example, students who are very interested in learning biology will study seriously and focus on learning biology so that cognitive biology learning outcomes can be maximized (Darmawan, Zubaidah, Ristanto, Zamzami, & Wahono, 2020;Refirman Djamahar, Rizhal Hendi Ristanto, & Ericka Darmawan, 2020;Ristanto, Djamahar, Heryanti, & Ichsan, 2020). Thus the interest in learning biology when learning biology online during the Covid-19 pandemic is very necessary for students to get good cognitive learning outcomes (Wicaksana, Atmadja, Wikanso, Putri, & Muthia, 2020).…”
Section: The Influence Of Learning Interests On Cognitive Learning Outcomes Of Students In Biology During the Covid-19 Pandemicmentioning
confidence: 99%
“…Berdasarkan penelitian yang dilakukan oleh [5], edmodo dapat menjadi solusi sebagai media pembelajaran yang dapat digunakan guru ditengah pandemi. Dalam proses pembelajaran secara daring edmodo efektif menjadi e-learning pilihan bagi guru untuk melaksanan proses pembelajaran.…”
Section: Delfira Dan Aldi DI Dalam Edmodounclassified